2018
DOI: 10.1186/s12889-018-5050-4
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of tobacco interventions for LGBTQ+ youth and young adults: overarching themes and key learnings

Abstract: BackgroundSmoking prevalence is very high among lesbian, gay, bisexual, transgendered and queer (LGBTQ+) youth and young adults (YYA) compared to non-LGBTQ+ YYA. A knowledge gap exists on culturally appropriate and effective prevention and cessation efforts for members of this diverse community, as limited interventions have been developed with and for this population, and there are very few studies determining the impact of these interventions. This study identifies the most salient elements of LGBTQ+ cessati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…The 20 articles included in this scoping review reported on 15 intervention programs, including a smoking cessation intervention for 'LGBT' smokers reported in two articles (Matthews, Breen, et al, 2019;Matthews, Steffen, et al, 2019), and a smoking cessation intervention for young LGBTQ people reported in three articles (Ramo et al, 2019;. Three of the articles described a single study that evaluated the acceptability of three hypothetical interventions, rather than delivery of actual interventions (Baskerville et al, 2016(Baskerville et al, , 2017(Baskerville et al, , 2018. We have organised the types of intervention described across this review into three categories: therapeutic (interventions based in clinic settings or involving therapeutic modalities; n = 9), online (interventions delivered via digital platforms and technologies; n = 7) and scene-based (interventions that took place at the material sites in which LGBTQ communities interact socially; n = 3).…”
Section: Re Sultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 20 articles included in this scoping review reported on 15 intervention programs, including a smoking cessation intervention for 'LGBT' smokers reported in two articles (Matthews, Breen, et al, 2019;Matthews, Steffen, et al, 2019), and a smoking cessation intervention for young LGBTQ people reported in three articles (Ramo et al, 2019;. Three of the articles described a single study that evaluated the acceptability of three hypothetical interventions, rather than delivery of actual interventions (Baskerville et al, 2016(Baskerville et al, , 2017(Baskerville et al, , 2018. We have organised the types of intervention described across this review into three categories: therapeutic (interventions based in clinic settings or involving therapeutic modalities; n = 9), online (interventions delivered via digital platforms and technologies; n = 7) and scene-based (interventions that took place at the material sites in which LGBTQ communities interact socially; n = 3).…”
Section: Re Sultsmentioning
confidence: 99%
“…We have organised the types of intervention described across this review into three categories: therapeutic (interventions based in clinic settings or involving therapeutic modalities; n = 9), online (interventions delivered via digital platforms and technologies; n = 7) and scene-based (interventions that took place at the material sites in which LGBTQ communities interact socially; n = 3). One article described the interventions spanning all three categories (Baskerville et al, 2018). Some articles did not explicitly include cancer prevention and/or screening as their primary rationale for the intervention but were included in this review because they aimed to reduce behaviours that we identified as being within the scope of cancer prevention for LGBTQ communities.…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations